Evaluation of the Nutrition Heart Program Through the Four Elements of Community Empowerment Approach - Rika Satyadewi; Galuh Mega Kurnia; Arina Mufida Ersanti; Corie Indria Prasasti (Amerta Nutrition)
Background: The Nutrition Heart Program is a community empowerment initiative implemented to enhance the weight of toddlers based on local food capabilities. The 2024 evaluation results revealed that 46.85% of participants experienced fluctuating weight trends. Narayan's four elements of community empowerment (access to information, inclusion/participation, accountability, local organizational capacity) play a crucial role in future program enhancements.